‘Asking for help’: a qualitative interview study exploring the experiences of interpersonal counselling (IPC) compared to low-intensity cognitive behavioural therapy (CBT) for women with depression during pregnancy - Jenny Ingram (BMC, 2021)
Abstract Background Treating depression early in pregnancy can improve health outcomes for women and their children. Current low-intensity psychological therapy for perinatal depression is a supported self-help approach informed by cognitive behavioural therapy (CBT) principles. Interpersonal counselling (IPC) may be a more appropriate low-intensity talking therapy for addressing the problems experienced by pregnant women with depression. A randomised feasibility trial (ADAGIO) has compared the acceptability of offering IPC for mild-moderate antenatal depression in routine NHS services compared to low-intensity CBT. This paper reports on a nested qualitative study which explored women’s views and expectations of therapy, experiences of receiving IPC, and Psychological Wellbeing Practitioners (PWPs - junior mental health workers) views of delivering the low-intensity therapy. Methods A qualitative study design using in-depth semi-structured interviews and focus groups. Thirty-two pregnant women received talking therapy within the ADAGIO trial; 19 contributed to the interview study from July 2019 to January 2020; 12 who had IPC and seven who had CBT. All six PWPs trained in IPC took part in a focus group or interview. Interviews and focus groups were recorded, transcribed, anonymised, and analysed using thematic methods. Results Pregnant women welcomed being asked about their mental health in pregnancy and having the chance to have support in accessing therapy. The IPC approach helped women to identify triggers for depression and explored relationships using strategies such as ‘promoting self-awareness through mood timelines’, ‘identifying their circles of support’, ‘developing communication skills and reciprocity in relationships’, and ‘asking for help’. PWPs compared how IPC differed from their prior experiences of delivering low-intensity CBT. They reported that IPC included a useful additional emotional component which was relevant to the perinatal period. Conclusions Identifying and treating depression in pregnancy is important for the future health of both mother and child. Low-intensity perinatal-specific talking therapies delivered by psychological wellbeing practitioners in routine NHS primary care services in England are acceptable to pregnant women with mild-moderate depression. The strategies used in IPC to manage depression, including identifying triggers for low mood, and communicating the need for help, may be particularly appropriate for the perinatal period. Trial registration ISRCTN 11513120. 02/05/2019.